An Analysis of Students Perception on the Use of Google Classroom in English Language Learning - Mega Triana; Herman Herman; Bloner Sinurat; Dumaris E. Silalahi (Cetta: Jurnal Ilmu Pendidikan, 2021)
The study's goal was to find out how students at SMK Negeri 1 Bandar Masilam felt about using Google Classroom to learn English and how easy it was to use. Google Classroom is one of the learning media. Google Classroom is a well-known tool in the education sector, particularly at the collegiate level. Google Classroom was used by some teachers as a learning medium. Google Classroom in language learning is being studied using qualitative research methods and a questionnaire as an instrument. Twenty students from SMK Negeri 1 Bandar Masilam's Class X Tkj-1 and X Tkj-2 will participate in the study. Research and discussion have shown that students' perceptions of Google Classroom use have a positive response. Most students agree that Google Classroom is easy to use and that it helps students learn English by allowing them to save and retrieve assignments and, in the case of Google Classroom, submit assignments. As a result, using Google Classroom to learn English is a wise decision.